2019
DOI: 10.1002/biot.201900203
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Site‐Specific PEGylation of Fibroblast Growth Factor 2 Facilitates Rational Selection of Conjugate Sites

Abstract: Polyethylene glycol modification (PEGylation) can enhance the pharmacokinetic properties of therapeutic proteins by the attachment of polyethylene glycol (PEG) to the surface of a protein to shield the protein surface from proteolytic degradation and limit aggregation. However, current PEGylation strategies often reduce biological activity, potentially as a result of steric hindrance of PEG. Overall, there are no structure-based guidelines for selection of conjugate sites that retain optimal biological activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…It has been reported that, in several cases, PEG molecules affect specific interactions of biomolecules with molecular targets. , In agreement, Zhao et al observed that PEGylation of FGF2 at sites located in close proximity to the receptor-binding region decreased the affinity to the receptor and heparin and affected its biological activities, such as activation of downstream signal transduction and stimulation of proliferation . We conjugated PEGylated drugs to cysteines separated from the primary and secondary FGFR1 binding sites (Figure S1).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It has been reported that, in several cases, PEG molecules affect specific interactions of biomolecules with molecular targets. , In agreement, Zhao et al observed that PEGylation of FGF2 at sites located in close proximity to the receptor-binding region decreased the affinity to the receptor and heparin and affected its biological activities, such as activation of downstream signal transduction and stimulation of proliferation . We conjugated PEGylated drugs to cysteines separated from the primary and secondary FGFR1 binding sites (Figure S1).…”
Section: Resultssupporting
confidence: 76%
“… 55 , 56 In agreement, Zhao et al observed that PEGylation of FGF2 at sites located in close proximity to the receptor-binding region decreased the affinity to the receptor and heparin and affected its biological activities, such as activation of downstream signal transduction and stimulation of proliferation. 57 We conjugated PEGylated drugs to cysteines separated from the primary and secondary FGFR1 binding sites 58 ( Figure S1 ). We validated that PEG4- and PEG27-based conjugates did not affect the interaction with isolated extracellular domains of FGFR1 ( Table 2 ) as well as FGFR1 on the surface of NIH 3T3 cells ( Figure 4 and Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…PEGylation was first introduced by Abuchowski and co-workers in 1977 and describes the covalent conjugation of one or multiple poly­(ethylene glycol) (PEG) chains to a protein in a random or site-specific manner, being already exploited to a large number of biomolecules. , The resulting PEG-protein conjugates exhibit longer circulation time, mainly due to diminished renal clearance and shielding of immunogenic protein epitopes, preventing fast depletion from the bloodstream. Within the last few years, PEG’s image as being a safe and nonimmunogenic polymer, however, has been challenged by numerous reports on the occurrence of anti-PEG antibodies ,, in clinic, diminishing the benefits of PEGylation, thereby compromising its therapeutic efficacy. , Therefore, manifold efforts to find alternative polymer platforms for protein conjugation, covering synthetic as well as biodegradable, natural polymer systems, have been made. , …”
Section: Introductionmentioning
confidence: 99%
“…Since most drug discovery approaches rely on competitive inhibitors targeting the catalytic pocket, these sites might allow an alternative route to develop irreversible and highly selective inhibitors. The site-specific PEGylation of the fibroblast growth factor 2 (FGF2) at Cys27 or Cys129 also led to drastic decrease in the binding to its receptor (Zhao et al, 2020). In this work, FGF2 which has 4 naturally occurring cysteine residues, was mutated in order to remove two surface exposed cysteine residues.…”
Section: Unveiling Druggable Pockets With Site-specific Protein Modifmentioning
confidence: 99%